Molecular investigation of genetic assimilation during the rapid adaptive radiations of East African cichlid fishes. Issue 23 (23rd November 2017) - Gunter, Helen M.; Schneider, Ralf F.; Karner, Immanuel; Sturmbauer, Christian; Meyer, Axel
Abstract: Adaptive radiations are characterized by adaptive diversification intertwined with rapid speciation within a lineage resulting in many ecologically specialized, phenotypically diverse species. It has been proposed that adaptive radiations can originate from ancestral lineages with pronounced phenotypic plasticity in adaptive traits, facilitating ecologically driven phenotypic diversification that is ultimately fixed through genetic assimilation of gene regulatory regions. This study aimed to investigate how phenotypic plasticity is reflected in gene expression patterns in the trophic apparatus of several lineages of East African cichlid fishes, and whether the observed patterns support genetic assimilation. This investigation used a split brood experimental design to compare adaptive plasticity in species from within and outside of adaptive radiations. The plastic response was induced in the crushing pharyngeal jaws through feeding individuals either a hard or soft diet. We find that nonradiating, basal lineages show higher levels of adaptive morphological plasticity than the derived, radiated lineages, suggesting that these differences have become partially genetically fixed during the formation of the adaptive radiations. Two candidate genes that may have undergone genetic assimilation, gif and alas1, were identified, in addition to alterations in the wiring of LPJ patterning networks. Taken together, our results suggest that genetic assimilation may have dampened the inducibility of plasticity related genes during the adaptive radiations of East African cichlids, flattening the reaction norms and canalizing their feeding phenotypes, driving adaptation to progressively more narrow ecological niches.